VALERIE: Um guia para elaboração de entrevistas semiestruturadas para avaliação de player experience em jogos baseados em localização - Lima, Nayana Thércia Carneiro (2019)
One of the key challenges for the gaming research community is the lack of appropriate methods and tools to measure entertainment experiences in a sensitive, reliable, and valid way. Games User Research (GUR) is a field of study that has sought to form a set of methods and techniques to evaluate the player interaction in various types of digital games. Aiming to add efforts to GUR advances, this research focuses on the study of Location-Based Games (LBGs), which in recent years have gained space in industry and academia, being applied in various areas, such as health, education, and tourism. Since LBGs have unique characteristics that set them apart from other conventional games (such as spatiality, mobility, and pervasiveness), evaluating the player interaction and experience with an LBG can be a real challenge. Hence, it is necessary to design and adapt methods for this domain. In this context, this dissertation proposes VALERIE (eVAluation of Location-based games and player Experience Interview guidE), a guide for the elaboration of semi-structured interviews to evaluate the player experience (PX) in LBGs, consisting of categories of questions, 60 topics to be addressed in interviews, and recommendations for this purpose. VALERIE was drawn from results obtained from literature reviews, a systematic mapping of the literature, an expert opinion survey, and adaptation of the semi-structured interview techniques proposed by Larry Wood (1997). Sixteen participants (nine experts and seven Human-Computer Interaction students) evaluated VALERIE's content, attested its adequacy and indicated improvements that were later applied in a refinement step. We hope VALERIE will help students, researchers, and practitioners plan and conduct PX evaluations in the LBGs context. We also expect that this work can contribute to the LBGs evaluation' maturing and disseminating GUR studies in academia.